Chemically chargeable photo battery - Thimmappa, Ravikumar; Paswan, Bhuneshwar; Gaikwad, Pramod; Devendrachari, Mruthyunjayachari Chattanahalli; Kotresh, Harish Makri Nimbegondi; Mohan, Ramsundar Rani; Alias, Joy Pattayil; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry C, 2015)
Here we show a surrogate strategy for power production, wherein light is used to actuate a discharge Chemistry in the cathode of an aqueous rechargeable battery (ARB). The proposed photo battery consists of a titaninm nitride photoanode, promising. cathode:material iron(III) hexacyanoferrate(II) as the battery active species, and Na2S2O8 as the chemical charging agent The photo battery delivered negligible capacity in the dark and the capacity shot up to 77.8 mAh/g when artificially shined light, confirming that the battery chemistry is light driven. In the ambient light, the device retained 72% of its artificial light discharge capacity with a stable cycling for more than 100 cycles. Further, an unprecedented means for charging the battery rapidly is presented using Na2S2O8 and it revitalized the battery in 30 s without any external bias. This methodology of expending a photoanode extends to a battery that is free from dissolution of active materials, irreversible structural changes, spontaneous deinsertion reactions, and safety concerns commonly encountered in the state of the art anode materials in ARBs. Apart from bringing out a sustainable way for power production, this device opens up avenues for charging the battery in the likely events of electrical input unavailability, while solving the critcial issues of longer charging time and higher charging voltage.

Solution chemistry-based nano-structuring of copper dendrites for efficient use in catalysis and superhydrophobic surfaces - Bakthavatsalam, Rangarajan; Ghosh, Subrata; Biswas, Ratul Kumar; Saxena, Aayushi; Raja, Alagar; Thotiyl, Musthafa Ottakam; Wadhai, Sandip; Banpurkar, Arun G.; Kundu, Janardan (RSC Advances, 2016)
Despite their performance and economic advantages over Ag and Au, there have been no focused research efforts on the nano-structuring of Cu dendrites with respect to fine-tuning their structure/morphology towards the efficiency enhancement of suitable applications. Reported here is a simple, versatile, environmentally-friendly and galvanic replacement reaction-based solution chemistry methodology to synthesize highly nano-structured copper dendrites targeted towards the efficiency enhancement of desired applications. Herein, copper is deposited galvanically on an Al foil in the presence of NaCl/HCl, wherein the chloride anions augment an uninterrupted replacement reaction. The growth process of Cu dendrites has been probed in detail. The presence of acid, the type of Cu2+ precursor salt, the Cu2+ ion concentration, the surfactant concentration and the reaction temperature are all demonstrated to provide useful means of modulating the surface structure/morphology of the dendrites. Notably, dendrites formed in the presence of acid are found to be highly nano-structured. Moreover, it is also found that the morphology/structure of the obtained Cu deposit depends considerably upon the choice of the Cu2+ precursor salt, a parameter that has been completely overlooked in the past. The acid-induced nano-structuring of the dendrites is exploited for enhancing their efficiency in the catalytic reduction of para-nitrophenol and for fabricating self-cleaning superhydrophobic surfaces. These nano-structured dendrites are demonstrated to have the highest ever normalized rate constant for the catalytic reduction reaction. Superhydrophobic surfaces fabricated using these dendrites demonstrate excellent self-cleaning abilities, showing a high contact angle (159 degrees) with low contact angle hysteresis (2 degrees). This facile synthetic strategy for the fabrication of highly nano-structured Cu dendrites is expected to open up avenues for the production of Cu-based low-cost functional nano/micro-materials.

Geometrical isomerism directed electrochemical sensing - Kottaichamy, Alagar Raja; Begum, Shabbah; Devendrachari, Mruthyunjayachar Chattanahalli; Bhat, Zahid Manzoor; Thimmappa, Ravikumar; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Analytical Chemistry, 2020)
We report the independent role of isomerism of secondary sphere substituents over their nature, a factor often overlooked in molecular electrocatalysis pertaining to electrochemical sensing, by establishing that isomerism redefines the electronic structure at the catalytic reaction center via geometrical factors. UV-vis spectroscopy and X-ray photoelectron spectroscopy suggest that a substituent's isomerism in molecular catalysts conjoins molecular planarity and catalytic activation through competing field effects and resonance effects. As a classical example, we demonstrate the influence of isomerism of the -NO2 substituents for the electrocatalytic multi electron oxidation of As(III), a potentially important electrochemical pathway for water remediation and arsenic detection. The isomerism dependent oxidative activation of catalytic center leads to a nonprecious molecular catalyst capable for direct As(III) oxidation with an experimental detection limit close to WHO guidelines. This work opens up an unusual approach in analytical chemistry for developing various sensing platforms for challenging chemical and electrochemical reactions.

Unprecedented isomerism-activity relation in molecular electrocatalysis - Kottaichamy, Alagar Raja; Begum, Shabbah; Nazrulla, Mohammed Azeezulla; Dargily, Neethu Christudas; Devendrachari, Mruthyunjayachari Chattanahalli; Bhat, Zahid Manzoor; Thimmappa, Ravikumar; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry Letters, 2020)
The role of electrocatalysts in energy storage/conversion, biomedical and environmental sectors, green chemistry, and much more has generated enormous interest in comprehending their structure-activity relations. While targeting the surface-to-volume ratio, exposing reactive crystal planes and interfacial modifications are time-tested considerations for activating metallic catalysts; it is primarily by substitution in molecular electrocatalysts. This account draws the distinction between a substituent's chemical identity and isomerism, when regioisomerism of the -NO2 substituent is conferred at the ``alpha'' and ``beta'' positions on the macrocycle of cobalt phthalocyanines. Spectroscopic analysis and theoretical calculations establish that the beta isomer accumulates catalytically active intermediates via a cumulative influence of inductive and resonance effects. However, the field effect in the alpha isomer restricts this activation due to a vanishing resonance effect. The demonstration of the distinct role of isomerism in substituted molecular electrocatalysts for reactions ranging from energy conversion to biosensing highlights that isomerism of the substituents makes an independent contribution to electrocatalysis over its chemical identity.

Regio-isomerism directed electrocatalysis for energy efficient zinc-air battery - Mukhopadhyay, Sanchayita; Devendrachari, Mruthyunjayachari Chattanahalli; Kanade, Sandeep C.; Vinod, Chathakudath Prabhakaran; Kotresh, Harish Makri Nimbegondi; Thotiyl, Musthafa Ottakam (iScience, 2022)
We have investigated the role of ligand isomerism in modulating the mechanisms and kinetics associated with charge/ discharge chemistry of an aqueous metal-air battery. The dominant electron-withdrawing inductive effect (-I effect) and the diminished electron-withdrawing resonance effect (-R effect) in the alpha-NO2 isomer noticeably diminishes the rate of oxygen reduction (ORR) and oxygen evolution reactions (OER) on the catalytic Co-center. In their beta-counterpart, the cumulative -I and -R effects noticeably enhance the OER and ORR kinetics on the same catalytic Co-center. Therefore, the regioisomerism of the -NO2 functionality amplifies the kinetics of ORR/OER without influencing their mechanistic pathways. When isomeric electrocatalysts are integrated to aid the charge chemistry of a Zn-air battery, the overpotential could be decreased by similar to 250mV with beta-NO2 isomer leading to a round-trip efficiency as high as 60%. This work contributes to the design of novel molecular platforms to target the overall round-trip efficiency of energy storage and conversion devices.

Unprecedented energy storage in metal-organic complexes via constitutional isomerism - Kottaichamy, Alagar Raja; Deebansok, Siraprapha; Deng, Jie; Nazrulla, Mohammed Azeezulla; Zhu, Yachao; Bhat, Zahid Manzoor; Devendrachari, Mruthyunjayachari Chattanahalli; Vinod, Chathakudath Prabhakaran; Kotresh, Harish Makri Nimbegondi; Fontaine, Olivier; Thotiyl, Musthafa Ottakam (Chemical Science, 2023)
The essence of any electrochemical system is engraved in its electrical double layer (EDL), and we report its unprecedented reorganization by the structural isomerism of molecules, with a direct consequence on their energy storage capability. Electrochemical and spectroscopic analyses in combination with computational and modelling studies demonstrate that an attractive field-effect due to the molecule's structural-isomerism, in contrast to a repulsive field-effect, spatially screens the ion-ion coulombic repulsions in the EDL and reconfigures the local density of anions. In a laboratory-level prototype supercapacitor, those with beta-structural isomerism exhibit nearly 6-times elevated energy storage compared to the state-of-the-art electrodes, by delivering similar to 535 F g(-1) at 1 A g(-1) while maintaining high performance metrics even at a rate as high as 50 A g(-1). The elucidation of the decisive role of structural isomerism in reconfiguring the electrified interface represents a major step forward in understanding the electrodics of molecular platforms.

Unusual ligand assistance in molecular electrocatalysis via interfacial proton charge assembly - Mukhopadhyay, Sanchayita; Kottaichamy, Alagar Raja; Chame, Pallavi Vyankuram; Ghosh, Prasenjit; Vinod, Chathakudath Prabhakaran; Makri Nimbegondi Kotresh, Harish; Kanade, Sandeep C.; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry Letters, 2023)
We show that the ability of the ligand to reorganizethe electricdouble layer (EDL) often dominates the electrocatalysis contrary totheir inductive effect in the spectrochemical series, leading to counterintuitiveelectrocatalysis. With water oxidation and chlorine evolution as theprobe reactions, the same catalytic entity with carboxy functionalizedligand exhibited surprisingly higher electrochemical activity in comparisonto the aggressively electron-withdrawing nitro functionalized ligands,which is contrary to their actual location in the spectrochemicalseries. Spectroscopic and electrochemical analyses suggest the enrichmentof catalytically active species in the carboxy substituted ligandvia proton charge assembly in the EDL that in turn enhances the kineticsof the overall electrochemical process. This demonstration of lessobvious ligands becoming indispensable in electrocatalysis suggestsa blind designing of ligands solely based on their inductive effectshould be reconsidered as it will prevent the utilization of the maximumpotential of the molecule in electrocatalysis.

Electrochemical energy storage in an organic supercapacitor via a non-electrochemical proton charge assembly - Mukhopadhyay, Sanchayita; Kottaichamy, Alagar Raja; Devendrachari, Mruthyunjayachari Chattanahalli; Mendhe, Rahul Mahadeo; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Chemical Science, 2024)
Contrary to conventional beliefs, we show how a functional ligand that does not exhibit any redox activity elevates the charge storage capability of an electric double layer via a proton charge assembly. Compared to an unsubstituted ligand, a non-redox active carboxy ligand demonstrated nearly a 4-fold increase in charge storage, impressive capacitive retention even at a rate of 900C, and approximately a 2-fold decrease in leakage currents with an enhancement in energy density up to approximately 70% via a non-electrochemical route of proton charge assembly. Generalizability of these findings is presented with various non-redox active functional units that can undergo proton charge assembly in the ligand. This demonstration of non-redox active functional units enriching supercapacitive charge storage via proton charge assembly contributes to the rational design of ligands for energy storage applications.

Fuel from waste: electrosynthesizing ammonia directly from agricultural digestate through ligand isomerization - Mendhe, Rahul Mahadeo; Mondal, Ritwik; Kottaichamy, Alagar Raja; Haridas, Akshay; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thimmappa, Ravikumar; Thotiyl, Musthafa Ottakam (Green Chemistry, 2024)
We demonstrate that the catalytic metal centre for ammonia production can be selectively activated with only a slight alteration in ligand isomerization (alpha and beta isomers), making it practical and effective even for agricultural effluents. With almost 90% faradaic efficiency, the beta isomer generates approximately 0.64 mg h-1 cm-2 of ammonia. Energy-efficient ammonia recovery is made possible by the interfacial proton charge assembly that beta-isomerization creates, which attracts the reacting nitrate and repels the competing hydronium ions. With minimal energy consumption, this isomerization approach can interconvert agricultural effluents into ammonia fuel, reaching up to 84% of its theoretical yield and maintaining stability over 100 hours of continuous electrolysis. Ligand isomerization driven ammonia electrosynthesis from agricultural waste water.

Ligand isomerization driven electrocatalytic switching - Kottaichamy, Alagar Raja; Nazrulla, Mohammed Azeezulla; Parmar, Muskan; Thimmappa, Ravikumar; Devendrachari, Mruthyunjayachari Chattanahalli; Vinod, Chathakudath Prabhakaran; Volokh, Michael; Kotresh, Harish Makri Nimbegondi; Shalom, Menny; Thotiyl, Musthafa Ottakam (ANGEWANDTE CHEMIE-INTERNATIONAL EDITION, 2024)
Keywords: Catalysts; CO2 reduction; O-2 REDUCTION; oxygen reduction

Switchable molecular electrocatalysis - Dutt, Shifali; Kottaichamy, Alagar Raja; Dargily, Neethu Christudas; Mukhopadhyay, Sanchayita; Nayak, Bhojkumar; Devendrachari, Mruthyunjayachari Chattanhali; Vinod, Chatakudhath Prabakaran; Kotresh, Harish Makri Nimbegondi; Thotiyl, Musthafa Ottakam (CHEMICAL SCIENCE, 2024)
Keywords: CO2 reduction; COBALT PHTHALOCYANINE; NANOPOROUS GOLD; oxygen reduction